"Hardwired" Biology and "Light Bulb" Moments: Divergent Life Course Trajectories and Discourses among Older Bisexual Women. Issue 4 (2nd October 2021) - Jen, Sarah
ABSTRACT: Little is known about the ways in which older bisexual individuals make meaning out of their sexual identity. This study examined narratives of older bisexual women from a life course perspective to better understand their life experiences and how their bisexual identities developed within historical and discursive contexts. In-depth interviews with bisexual-identified older women (age 60+) were analyzed using a 6-step Foucauldian discourse analysis process. Two groups of women emerged in the data, distinguished by the timing of their first attractions to women and their constructions of bisexuality. The Early Emergers were characterized by their early attractions to women and emphasis on biological constructions, while the Midlife Migrators recognized their attractions to women relatively later and described bisexuality as a social construction. Findings indicate the need for multiple legible narratives of bisexuality and the need to examine historical context and timing of lives as indicators of potential challenges and strengths.